PENINGKATAN PRESTASI BELAJAR BAHASA INDONESIA MELALUI MEDIA GAMBAR PADA TEMA BUDI PEKERTI MATERI BERCERITA SISWA KELAS II SDN KEDONDONG 2 GAJAH DEMAK - Saidun Saidun (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
The purpose of this class action research is to find out how far the improvement of student achievement in SDN Kedondong 2 through the use of media images. In this action research is done in 3 cycles, from the result of action done proven to improve student achievement by reaching ideal standard. From 59.57% in Cycle I, it can increase to 64.35% in cycle II, and the third cycle increased to 77.83%. The results of this action study indicate that the use of media images in Indonesian language lessons can improve student achievement on the material tells the story with completeness reached 91%. The students' response to the Indonesian language learning on the theme of the material mind tells the story by using very positive image media. It can be concluded that the improvement of Indonesian language learning achievement through effective drawing media applied to students in SDN Kedondong 2 Gajah Demak.